Is it a gut feeling?: bodily sensations associated with the experience of valence and arousal in patients with inflammatory bowel disease - Atanasova, Konstantina; Lotter, Tobias; Bekrater-Bodmann, Robin; Kleindienst, Nikolaus; Reindl, Wolfgang; Lis, Stefanie (Frontiers in psychiatry, 2022)
BackgroundPrevious studies have shown dysfunctional emotion processing in patients with inflammatory bowel diseases (IBD), characterized by a hypersensitivity to negative emotions and a hyposensitivity to positive emotions. Models of emotion processing emphasize the importance of bodily sensations to the experience of emotions. Since there have been no studies on whether emotion-associated bodily sensations are changed in IBD, we investigated the experience of bodily sensations related to valence and arousal, together with their links to emotional awareness, as one domain of interoceptive sensibility relevant to emotion processing.MethodsUsing a topographical self-report measure, 41 IBD patients in clinical remission and 44 healthy control (HC) participants were asked to indicate where and how intensely in their body they perceive changes when experiencing emotions of positive and negative valence, as well as relaxation and tension. Additionally, we used self-report questionnaires to assess emotional awareness as one domain of an individual’s interoceptive sensibility, gastrointestinal-specific anxiety (GSA), and psychological distress.ResultsPatients with IBD reported higher emotional awareness but lower intensities of perceived changes in their bodily sensations related to valence and arousal of emotional processing. IBD patients reported less intense bodily activation during positive emotions and less intense bodily deactivation during negative emotional states in comparison to HC participants. Higher emotional awareness and psychological distress were linked to stronger experiences of emotion-related bodily sensations in IBD patients.ConclusionInflammatory bowel diseases patients exhibited alterations in how they link bodily sensations to their emotional experience. Such persistent changes can affect a patient’s wellbeing and are related to higher levels of anxiety and depression among IBD patients, even in remission.
Gesehen am 04.11.2022